The effects of quality control system on professional skepticism and its implications to audit quality with peer review as a moderating variable (A case study on Public Accounting Firms in Semarang) - Hafidz Ridloi (Journal of Islamic Accounting and Finance Research, 2021)
Purpose - This study aims to assess the role of CPA Firms related to the quality control system in maintaining the professional skepticism level of auditors affecting the quality of audits provided by the Public Accountants.Method - Population and samples used in this research were the whole auditors working for the CPA Firms in Semarang. The researcher collected the samples using a purposive sampling technique. The number of samples in this study was 31 auditors. The researcher collected the data using online questionnaires sent through email to each CPA Firm. Data analysis was conducted using a Structural Equation Modeling - Partial Least Square (SEM-PLS) with WarpPLS 4.0 software.Result - The results of this study indicated that the quality control system did not affect the auditor’s professional skepticism. Peer review did not moderate the quality control system. The auditor's professional skepticism variable has a significant effect on audit quality. Then, quality control system did not affect audit quality through auditor’s professional skepticism.Implication - To maintain audit quality, CPA Firms in Semarang needs to improve the competence, experience, and professionalism of auditors performing the audit assignments that the professional skepticism of the concerned personnel can be properly maintained.Originality - This study has presented a moderating variable in the relationship between peer review and quality control system affecting professional skepticism.